Fechner (1866): The Aesthetic Association Principle—A Commented Translation. (May 2020) - Ortlieb, Stefan A.; Kügel, Werner A.; Carbon, Claus-Christian
Most of the groundbreaking works of Gustav Theodor Fechner (1801–1887), who paved the way for modern experimental psychology, psychophysics, and empirical aesthetics, are so far only available in German. With the first full text translation of Fechner's article on The Aesthetic Association Principle ( Das Associationsprincip in der Aesthetik ), we want to fill in one of the blank spots in the reception of his Aesthetics from Below (Aesthetik von Unten). In his 1866 article, Fechner devises a fundamental principle that accounts for the role of associations in the formation of aesthetic preferences. Based on concrete everyday examples and thought experiments, he demonstrates how aesthetic choices are largely shaped by the observer's learning history (associative factors) rather than by an object's formal properties (direct factors). Fechner's Aesthetic Association Principle has lost nothing of its initial relevance as the role of content and personal meaning is still grossly underrated in theory and practice of empirical aesthetics today.